PERAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN MINAT BELAJAR SISWA DISEKOLAH DASAR - Kasumo Dwi Ayu Rindika Putri; Siti Nurhalizah; Amiliah Amiliah (Kampus Akademik Publiser, 2025)
Learning media has a crucial role in increasing students' interest in learning, especially at the elementary school level. The use of appropriate media, such as images, videos, educational games and digital technology, helps students understand lesson material more easily. Apart from that, learning media makes the learning process more interesting, interactive and fun. This article aims to examine the role of learning media in increasing elementary school students' learning motivation and its impact on their academic achievement. This research was conducted using qualitative methods through a literature study approach to analyze various research related to learning media.